The Truncated Human Telomeric Sequence forms a Hybrid‐Type Intramolecular Mixed Parallel/antiparallel G‐quadruplex Structure in K+ Solution. (9th March 2016) - Liu, Yuxia; Cheng, Dengfeng; Ge, Min; Lin, Weizhen
Abstract : In 80–90% tumor cells, telomerase becomes active and stabilizes the length of telomeres. The formation and stabilization of G‐quadruplexes formed from human telomeric sequences have been proved able to inhibit the activity of telomerase, thus human telomeric G‐quadruplex structure has become a potential target for the development of cancer therapy. Hence, structure of G‐quadruplex formed in K + solution has been an attractive hotspot for further studies. However, the exact structure of human telomeric G‐quadruplex in K + is extremely controversial, this study provides information for the understanding of different G‐quadruplexes. Here, we report that 22nt and 24nt human telomeric sequences form unimolecular hybrid‐type mixed parallel/antiparallel G‐quadruplex in K + solution elucidated utilizing Circular Dichroism, Differential Scanning Calorimetry, and gel electrophoresis. Moreover, individual configuration of these two sequences was speculated in this study. The detailed structure information of the G‐quadruplex formed under physiologically relevant condition is necessary for structure‐based rational drug design. Abstract : In this paper, we report two G‐quadruplexes formed from (A) 22nt sequence and (B) 24nt sequence in K + solution. The detailed structure information is necessary for structure‐based rational drug design.